Why I am a catholic - Wills, Garry (Houghton Mifflin, 2002)
In this provocative work, which could not be timelier, Garry Wills, one of our country's most noted writers and historians, offers a powerful statement of his Catholic faith. Beginning with a reflection on his early experience of that faith as a child and later as a Jesuit seminarian, Wills reveals the importance of Catholicism in his own life. He goes on to challenge, in clear and forceful terms, the claim that criticism or reform of the papacy is an assault on the faith itself. For Wills, a Catholic can be both loyal and critical, a loving child who stays with his father even if the parent is wrong.